The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1161/01.cir.85.3.916
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary stenting for acute and threatened closure complicating percutaneous transluminal coronary angioplasty.

Abstract: BACKGROUND. Acute closure remains a significant limitation of percutaneous transluminal coronary angioplasty (PTCA) and underlies the majority of ischemic complications. This study details the clinical and angiographic characteristics of a series of patients receiving an intracoronary stent device to manage acute and threatened closure and presents the early clinical results. METHODS AND RESULTS. From October 1989 through June 1991, 115 patients undergoing PTCA received intracoronary stents to treat acute or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
185
2
13

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(205 citation statements)
references
References 38 publications
4
185
2
13
Order By: Relevance
“…The results from a consecutive series of patients like ours and randomized trials confirm the superiority of stents to balloon PTCA, both in the hospital and late followup outcomes. In the presence of some high-risk subgroups of patients, such as those with diabetes [20][21] , unstable angina 7 , acute myocardial infarction [15][16][17][18][19] , vessels with reference size <3.0mm 7 , balloon PTCA failures 6 , lesions located in he proximal left anterior descending artery 7,22 , chronic occlusions [13][14] , vein grafts 11 , restenotic lesions 12 and multivessel coronary disease 23 , who undergo percutaneous coronary revascularization, stents will promote better results and should be the technique of first choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from a consecutive series of patients like ours and randomized trials confirm the superiority of stents to balloon PTCA, both in the hospital and late followup outcomes. In the presence of some high-risk subgroups of patients, such as those with diabetes [20][21] , unstable angina 7 , acute myocardial infarction [15][16][17][18][19] , vessels with reference size <3.0mm 7 , balloon PTCA failures 6 , lesions located in he proximal left anterior descending artery 7,22 , chronic occlusions [13][14] , vein grafts 11 , restenotic lesions 12 and multivessel coronary disease 23 , who undergo percutaneous coronary revascularization, stents will promote better results and should be the technique of first choice.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison demonstrates that, stents can create significancy higher coronary lumen diameters, reduce the restenosis rate at the end of the first 6 months and as a consequence the need for further revascularization procedures, percutaneous or surgical, compared with the standard balloon PTCA method [4][5][6][7] . In 1995, Colombo et al 8 demonstrated that intravascular ultrasound could optimize stent delivery and implantation, applying higher balloon pressures (>12 ATM), promoting better stent symmetry, with a nearly full apposition of the stent struts in the vessel wall.…”
mentioning
confidence: 99%
“…Stents have been shown to successfully treat acute or threatened vessel closure after failed PTCA 6) and to significantly reduce restenosis. [7][8][9] Adjunctive use of potent antiplatelet agents such as ticlopidine or clopidogrel markedly decreased the incidence of stent thrombosis and bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary stent implantation along with balloon angioplasty is highly effective in the treatment of acute vessel closure (Sigwart et al 1987;Roubin et al 1992;de Jaegere et al 1993a;Fischman et al 1994). However, bare metal stents are thrombogenic, and the benefit achieved at the expense of high-risk vascular complications (Schatz et al 1991;Serruys et al 1994;de Jaegere et al 1993b;Serruys et al 1991) must be considered.…”
Section: Hypothesismentioning
confidence: 99%